2007
DOI: 10.1038/sj.emboj.7601700
|View full text |Cite
|
Sign up to set email alerts
|

Autoprocessing of the Vibrio cholerae RTX toxin by the cysteine protease domain

Abstract: Vibrio cholerae RTX is a large multifunctional bacterial toxin that causes actin crosslinking. Due to its size, it was predicted to undergo proteolytic cleavage during translocation into host cells to deliver activity domains to the cytosol. In this study, we identified a domain within the RTX toxin that is conserved in large clostridial glucosylating toxins TcdB, TcdA, TcnA, and TcsL; putative toxins from V. vulnificus, Yersinia sp., Photorhabdus sp., and Xenorhabdus sp.; and a filamentous/hemagglutinin-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
118
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 37 publications
3
118
0
Order By: Relevance
“…2), indicating that autoprocessing is a defining feature of this family of toxins. Detailed alignments show that all MARTX toxin CPDs include the histidine and cysteine that comprise the catalytic dyad, indicating that all of them could be enzymatically functional (30). Thus, it seems that all MARTX toxins have the propensity for autocatalytic cleavage.…”
Section: Autoprocessing Of Martx Toxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…2), indicating that autoprocessing is a defining feature of this family of toxins. Detailed alignments show that all MARTX toxin CPDs include the histidine and cysteine that comprise the catalytic dyad, indicating that all of them could be enzymatically functional (30). Thus, it seems that all MARTX toxins have the propensity for autocatalytic cleavage.…”
Section: Autoprocessing Of Martx Toxinsmentioning
confidence: 99%
“…Since autocleavage would not be expected until after translocation, it is not surprising that activation of the protease in vitro required addition of eukaryotic cell cytosol preparations. It was subsequently shown that binding, but not hydrolysis, of GTP was sufficient to stimulate processing, indicating that processing occurs after transit of the toxin to the eukaryotic cytoplasm with high GTP concentrations (30).…”
Section: Autoprocessing Of Martx Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of R. insecticola 5.15 encodes eight putative proteins with significant NCBI Conserved Domain RPS-BLAST hits to RTX toxins and related Ca 2+ -binding proteins (COG2931). In H. defensa and both R. insecticola strains, putative RTX (COG2931) genes also encode cysteine protease effector domains toward the N terminus for both C80 and M10 families, as in Yersinia pseudotuberculosis (Sheahan et al 2007). R. insecticola 5.15 encodes several RTX toxins with homologs present in H. defensa or R. insecticola LSR1 (Table 4).…”
Section: Exotoxins and Type I Secretion Systems ( T1ss)mentioning
confidence: 99%
“…This region was identified based on homology with the cysteine protease domain (CPD) found in the multifunctional autoprocessing repeats in toxins (MARTX) toxins from Gram-negative bacteria (14). Autoprocessing in the MARTX toxin from Vibrio cholera (VcRTx) is also stimulated by InsP6 (15).…”
mentioning
confidence: 99%